"I had to live, breathe, and write my character": Character Selection and Student Engagement in an Online Role-Play Simulation. Issue 4 (2nd October 2017) - Rector-Aranda, Amy; Raider-Roth, Miriam; Glaser, Noah; Behrman, Matthew
ABSTRACT: This study explores the relationship between character selection and student engagement in the Jewish Court of All Time (JCAT), an online and classroom-based role-playing simulation of a current events court case with Jewish historical roots. Analyzing students' responses to three questions posed in an out-of-character JCAT discussion forum, we tracked indications of their different types and styles of engagement and how they were associating this engagement with their character roles. The findings seek to augment the implementation of future JCAT simulations, as well as to inform research and practice of role-play simulations that involve assuming character personas.